PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA PADA KOPDIT CU MANDIRI TEBING TINGGI - Simangunsong, Elisabeth; Saragih, Joana L.; Purba, Betniar; Purba, Imelda R (UNIKA Santo Thomas, 2021)
The purpose of this study was to analyze the effect of compensation and work environment on employee morale at the CU Mandiri Tebing Tinggi Kopdit. Benefits of Research: Provide information material to the management of CU Mandiri Tebing Tinggi Kopdit about the effect of compensation and work environment on employee morale and For other researchers it can be used as a reference in conducting studies or research with the same subject matter as well as input for interested parties directly with this research. The number of samples was 96 respondents, the method of collecting data was through questionnaires and documentation, the variables studied were about the effect of compensation and work environment on employee morale at the Cooperative Unit of CU Mandiri Tebing Tinggi partially and simultaneously on work morale and data analysis methods with multiple regression. The results showed the linear regression equation: Linear regression equation: SK = 0.558 + 0.797Kom + 0.448LK., indicating the regression coefficient of the compensation variable (Kom) and work environment (LK), which was positive, meaning that all variables had a positive influence on work morale. The correlation coefficient (R) = 0.886, which means that the relationship between the compensation variable (Kom) and the work environment (LK) on work morale is very strong. The coefficient of determination (R2) = 0.785 means that the variable compensation (Kom) and work environment (LK) is able to explain 78.5% of work morale, while 21.5% is influenced by other factors. The calculated t value of the compensation variable = 6.871 and the work environment = 3.273 > t table which shows a significance number of 0.000 < 0.05, then the two variables have a partially significant effect on work morale. The calculated F value = 83.058 > F table with a significance level of 0.000 < 0.05, then Ho is rejected and H1 is accepted, meaning that the compensation variable (Kom) and work environment (LK) have a significant effect simultaneously on work morale. Based on the conclusion above, it is better if the Cooperative of CU Mandiri Tebing Tinggi needs to increase the compensation provided and the work environment to encourage employee morale so as to create job satisfaction. , Judging from the value of the coefficient of determination (R2) = 0.785, it means that compensation and work environment variables are able to explain 78.5% of work spirit while 21.5% is influenced by other factors. Other factors that affect morale should be investigated from the internal and external environment.